Could a cave hyena have made a musical instrument? A reply to Cajus G. Diedrich - Turk, Ivan; Turk, Matija; Toškan, Borut (Arheološki vestnik, 2016)
The contribution is a reply to the article written by Cajus G. Diedrich and published online on the web site of the Royal Society Open Science. Diedrich’s article is fraught with factual errors and underestimations of the archaeological and musicological findings. As such, it may cause great scientific damage and should thus not remain uncommented. Only the most prominent errors are addressed.